Improving or overturning the ITQ system? Views of stakeholders in Icelandic fisheries - Kokorsch, Matthias; Karlsdóttir, Anna; Benediktsson, Karl (BioMed Central Ltd., 2015)
Abstract Icelandic fisheries have gone through tremendous changes since the 1980s and the gradual implementation of individual transferable quotas. The paper investigates to what extent the power of different stakeholders in the fisheries management system has changed, and examines whether and in which fields enhanced participation is favoured by relevant stakeholder groups. Strengths and weaknesses of participation within the system are scrutinized and alternatives assessed. The analytical framework stems from the concept of adaptive co-management, whereas the empirical data derives from a survey on Icelandic fisheries management among important stakeholder groups. This survey showed that the critique of individual transferable quotas is not homogeneous. Regional differences are present regarding the evaluation of the current regime, but also of proposed alternative management instruments. Overall, more stakeholder participation, especially in data gathering and decision making, is demanded. This has in fact decreased over time. The authors suggest that the perceived shortcomings of the quota system in general and the lack of stakeholder participation in particular, can be addressed by adopting certain elements of adaptive co-management.